ANALYSIS OF MAINTENANCE PLANNING C01 CHECK IN AIRBUS A320-214 PK-LUM AT BATAM AERO TECHNIC (BAT) - Hazhiyah, Rika Raudhatul; Pinandhita, Lazuardy Rahendra; Mulyani, Sri (Institut Teknologi Dirgantara Adisutjipto, 2022)
Maintenance is all activities undertaken to maintain the aircraft, its aircraft components and equipment in an air condition including inspection, repair, servicing, overhaul and part change. To be able to perform maintenance properly, every aircraft is required to have a maintenance program. . Batam Aero Technic (BAT) handles MRO work on Airbus A320-214 aircraft with registration number PK-LUM. By analyzing the results of the aircraft maintenance planning to find out the comparison of the results of the planning with the implementation of maintenance. This can maximize the implementation of future maintenance so as not to interfere with aircraft flight operations at Batam Aero Technic (BAT). Before carrying out the treatment process, you should do the planning in advance to ensure that the treatment process runs in accordance with the planning made. To find out the treatment process is running in accordance with its planning or not, it will be analyzed using a fiishbone diagram. Fishbone diagrams are generally used in the stage of identifying problems and determining the cause of the problem. This treatment planning analsis process includes analysis of C01 check care implementation, evaluation of the implementation of C01 check treatment program, treatment delay solution, and C01 check care planning. Then from the results of the analysis the author obtained the cause of delays that occur in the field that is difficult to control such as the problem of delays in the availability of materials / spare parts where ordering and delivery time is needed. Therefore the authors propose to multiply the estimated manhours by 2.5 as an alternative to the anticipation of delayed completion of treatment. This is done to minimize the occurrence of delays in manhours on the ground.